2016
DOI: 10.1111/jcpp.12659
|View full text |Cite
|
Sign up to set email alerts
|

Association between irritability and bias in attention orienting to threat in children and adolescents

Abstract: Irritability in children is associated with biased attention toward threatening information. This finding, if replicated, warrants further investigation to examine the extent to which it contributes to chronic irritability and to explore possible treatment implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 68 publications
1
30
1
1
Order By: Relevance
“…In these studies, the face stimulus is presented for a relatively brief period (e.g., 17–1250 ms) and serves as a distractor. Dot probe studies in both clinical and community samples of irritable youth find an attention bias toward angry faces [19,20]. Similar findings manifest in youth with anxiety disorders and have given rise to a treatment (attention bias modification training) designed to decrease anxiety by reversing the threat bias [21,22].…”
Section: Social Information Processing In Irritable Youthmentioning
confidence: 99%
“…In these studies, the face stimulus is presented for a relatively brief period (e.g., 17–1250 ms) and serves as a distractor. Dot probe studies in both clinical and community samples of irritable youth find an attention bias toward angry faces [19,20]. Similar findings manifest in youth with anxiety disorders and have given rise to a treatment (attention bias modification training) designed to decrease anxiety by reversing the threat bias [21,22].…”
Section: Social Information Processing In Irritable Youthmentioning
confidence: 99%
“…Severe irritability has been associated with increased orientation toward threatening stimuli. For example, there is evidence that irritable children are more likely to direct attention to angry faces than are healthy volunteers (Hommer et al., ; Salum et al., ). Moreover, compared with healthy children, irritable children tend to interpret ambiguous or neutral facial stimuli as threatening (Brotman et al., ; Stoddard et al., ).…”
Section: Mechanisms Underlying Irritability and Their Clinical Relevancementioning
confidence: 99%
“…Finally, although not strictly a limitation, in the current study we used an emotion recognition task. Therefore, our study is not directly comparable to other studies that used paradigms to examine attentional bias (Hommer et al, 2014;Salum et al, 2017) or interpretation bias (Brotman et al, 2010;Guyer et al, 2007;Stoddard et al, 2016), the latter usually tested with neutral or ambiguous stimuli. However, the misidentifications in the current task were with regards to specific emotions, such as fear and anger, and not randomly distributed across all possible emotions; this suggests that errors were emotion specific, like the ones seen in attentional and interpretation bias paradigms (Bourke et al, 2010).…”
Section: Discussionmentioning
confidence: 61%
“…Specifically, a recent study found that the association between irritability and threat bias was independent of anxiety symptoms, as well as symptoms of attention hyperactivity disorder, conduct disorder, and oppositionality. However, this association was not independent from broad internalizing symptoms—defined as withdrawing symptoms, somatic complaints, and anxious/depressed symptoms (Salum et al., ).…”
Section: Introductionmentioning
confidence: 99%